Self-employment of foreigners as an innovative solution on the labor market in the European Union - Valentinas Navickas; Eva Grmanová; Waldemar Gajda (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The main aim of this article is to identify certain specificity in self-employment of foreigners in EU countries and to find out whether the differences in self-employment of foreigners between countries are diminishing. Within the main objective, we have set two sub-objectives. The first sub-objective is to compare EU countries on the basis of the following indicators: 1/ number of self-employed foreigners and 2/ share of self-employed foreigners in employed persons from foreign countries. The second sub-objective is to determine whether EU countries converge in the number of the share of self-employed foreigners in the number of employed persons from foreign countries. We have confirmed that the countries have a tendency to convergence in regard to the share of self-employed foreigners in employed persons from foreign countries. We assume that this tendency can also be due to the pressure of the labour market that shows a lack of labour force. The share of self-employed migrants is relatively high in Eastern Europe. On the other hand, their increase is below average compared to the EU.
Keywords: J61; 650; migration; self-employment; foreigners; immigrants; beta-convergence; correlation diagram; European Union